(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
According to the Philippine Statistics Authority (2022), the employment rate of the youth for August 2022 has already reached its highest point at 89.2%, which means that out of the 7.64 million youth with ages ranging from 15-24, 6.81 million are already employed. With these high numbers, along with the return of face-to-face classes, the probability of having more working students is troubling. The study entitled “Comparative Study of the Academic Stress and Anxiety Among Working and Non-working College Students” aimed to compare the lived experiences of the students in terms of their academic stress and anxiety. The data obtained from the interviews were then interpreted through Thematic Analysis, which required the data to produce themes that are relevant to the main variables of the study – Academic Stress and Anxiety. The findings obtained are specific only to the selected two groups of respondents – Working/Part-time Students & Nonworking/Full-time Students, in which seven themes were constructed to compare the two groups. Based on the themes formulated from the data obtained from the Working and the Non- working College Students, it was concluded that both groups tend to have different levels since more factors contribute to the stress and anxiety of the working students than the non- working students.